Contract Enforcement in Transition - Simon Johnson; John McMillan; Christopher Woodruff (Center for Economic Studies and ifo Institute (CESifo), 1999)
The mix of formal and informal mechanisms for contract enforcement is examined using survey data from Russia, Ukraine, Romania, Poland, and Slovakia. Using the size of trade credit to quantify the success of contracting, we ask: Do the courts have a perceptible effect on contracting? When can a firm rely on its customer to repay trade credit voluntarily? Which is more effective, the courts or relational contracting? Do trade associations play a role in contract enforcement? Does relational contracting entail inefficiencies? Is the reliance on relation contracting merely a transitory phenomenon, reflecting the inadequacy of these countries' legal systems?
Keywords: 330